Prevalencia de retraso del desarrollo infantil en prematuros tardíos a los 6 meses de edad - Montalván Miranda, Fernanda De Fátima (2017)
Late preterm infants (LP) present short and long-term complications, including developmental delay. A cross - sectional and descriptive study was carried out to determine the prevalence of developmental delay in late preterm infants at 6 months of chronological age. Material and Method: The sample consisted of 71 late preterm infants who were born at the "Hospital Belén de Trujillo" from January to June 2016. The sample size was determined using 5% of accuracy and a 95% confidence level. The level of overall developmental delay and in each of the areas of the Battelle Inventory: Personal Social, Adaptative, Motor, Communication and Cognitive were determined when the late premature was 6 months of chronological age. Results: We found a prevalence of 9.9% of developmental delay in preterm infants at 6 months of chronological age. The developmental delay in each area was: In Personal Social 8.5%, Adaptative 7%, Motor 12.7%, Communication 5.6% and Cognitive 11.3%. The highest percentage of delay was found in LPs born at 34 weeks of gestation (WG) and a significant difference was found with the prevalence of developmental delay in LP born at 35 WG and 36 WG. Conclusions: The prevalence of developmental delay in late preterms at 6 years of chronological age was 9.9%